2015
DOI: 10.1016/j.bcp.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Quilamine HQ1-44, an iron chelator vectorized toward tumor cells by the polyamine transport system, inhibits HCT116 tumor growth without adverse effect

Abstract: Tumor cell growth requires large iron quantities and the deprivation of this metal induced by synthetic metal chelators is therefore an attractive method for limiting the cancer cell proliferation. The antiproliferative effect of the Quilamine HQ1-44, a new iron chelator vectorized toward tumor cells by a polyamine chain, is related to its high selectivity for the Polyamine Transport System (PTS), allowing its preferential uptake by tumoral cells. The difference in PTS activation between healthy cells and tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Thus the seeking of low-toxic iron chelators or alternative measures, such as exogenous transferrin, exogenous hepcidin, hepcidin analogues, and hepcidin signaling agonists, continues ( Fleming and Ponka, 2012 ). Recent studies reported that novel iron chelators like CN128 ( Sun et al, 2020 ; Chen et al, 2020 ), Quilamine HQ1-44 ( Renaud et al, 2015 ), 1-(N-acetyl-6-aminohexyl)-3-hydroxy-2-methylpyridin-4-one ( Pangjit et al, 2015 ), and some phytochemicals like curcuminoids ( Jiao et al, 2009 ) and quercetin ( Horniblow et al, 2017 ), showed protective functions in many diseases by chelating iron, with no or little side effects. Our study highlighted the use of an iron-deficient diet to induce iron deficiency in restricting ferroptosis and preventing liver injuries, which was harmless than iron chelators because the non-existed side effects and the degree of iron deficiency would not be overwhelmed, for the reason that the iron deficiency induced by iron-deficient diet will increase the iron absorption and the majority of iron source is from the recycle use of iron in aged erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the seeking of low-toxic iron chelators or alternative measures, such as exogenous transferrin, exogenous hepcidin, hepcidin analogues, and hepcidin signaling agonists, continues ( Fleming and Ponka, 2012 ). Recent studies reported that novel iron chelators like CN128 ( Sun et al, 2020 ; Chen et al, 2020 ), Quilamine HQ1-44 ( Renaud et al, 2015 ), 1-(N-acetyl-6-aminohexyl)-3-hydroxy-2-methylpyridin-4-one ( Pangjit et al, 2015 ), and some phytochemicals like curcuminoids ( Jiao et al, 2009 ) and quercetin ( Horniblow et al, 2017 ), showed protective functions in many diseases by chelating iron, with no or little side effects. Our study highlighted the use of an iron-deficient diet to induce iron deficiency in restricting ferroptosis and preventing liver injuries, which was harmless than iron chelators because the non-existed side effects and the degree of iron deficiency would not be overwhelmed, for the reason that the iron deficiency induced by iron-deficient diet will increase the iron absorption and the majority of iron source is from the recycle use of iron in aged erythrocytes.…”
Section: Discussionmentioning
confidence: 99%